Chesterton on Play, Work, Paradox, and Christian Orthodoxy. Issue 1 (2nd January 2018) - Kretchmar, Scott; Watson, Nick J.
Abstract: In this essay we attempt to accomplish two things related to the work of G.K. Chesterton. The first is to use one of his favorite ploys to articulate the nature of play. We discuss several paradoxical characteristics of play and attempt to show how seemingly contradictory features actually help us to understand play's allure and other values. We introduce the second topic of theological analyses of work and play with a review of the Christian literature on these subjects. We then employ Chesterton's paradoxical theology to see how these two aspects of living might come to life and how people of faith should experience them.